Green supply chain management: a review and research direction - Abu Seman, Noor Aslinda; Zakuan, Norhayati; Jusoh, Ahmad Yusni; Md Arif, Mohd Shoki (2012)
Green Supply Chain Management (GSCM) has appeared as an environmental innovation which integrates environmental concerns into supply chain management. GSCM has gained popularity with both academic and practitioners. The purpose of the paper is to briefly review the recent literatures of the GSCM and also determine the new direction area of this emerging field. A detailed review is used to sort out the literature and develop the research direction of the study. The review is focused on development of GSCM in a developed and developing countries including all those researchers which is relevant to environmental and social sustainability towards operation management and the supply chain. It shows that lack researches to examine the adoption and implementation of GSCM practices especially in developing countries such as Malaysia. Thus, the authors bring forward a proposed research direction on GSCM adoption and implementation in Malaysia’s manufacturing industries.